Unmarried Adolescents’ Experiences of Using Reproductive and Maternal Health Services in Nigeria and Uganda: A Qualitative Study - Franklin Onukwugha; Peninah Agaba; Mark Hayter; Bev Orton (Social Sciences, 2022)
Adolescents’ access and use of reproductive and maternal health (RMH) services is a critical part of the global strategy for achieving the Sustainable Development Goals (SDGs). However, previous studies have shown that a complex range of factors, including restrictive policies and punitive laws, limit adolescents from accessing a full range of RMH services in Sub-Saharan Africa (SSA). Our study explores the experiences of unmarried adolescents’ access and use of RMH services in Nigeria and Uganda to understand the extent to which the diverse policy environment in both countries enables or hinders adolescents’ access to and use of RMH services. Our qualitative research design involved eight focus group discussions (FGDs) in Nigeria and in Uganda, 14 in-depth interviews, and eight FGDs among adolescents. The data were analysed thematically and organised according to the WHO’s five broad dimensions for assessing youth-friendly health services. Our findings show that RMH services were inequitably delivered in both countries. Adolescents were restricted from accessing services based on age and marital status. Being unmarried and having no partner, especially in Uganda, was a cause for discrimination during antenatal appointments. We also observed that the expectations of adolescents were not adequately met. Service providers tended to be impolite, judgemental, and unwilling to provide services, especially contraceptives, to younger and unmarried adolescents. Our findings suggest that the existence of a youth-friendly health policy does not translate into effective youth-friendly service provision. This underscores the need for further studies to understand the complexities surrounding this by using a realist evaluation method to examine how adolescent and youth-friendly health services can be designed to improve uptake of reproductive and maternal health services among adolescents in Sub-Saharan Africa.